Development of CNTs and ZnO-PVA Electromagnetic Detectors - Ahmad Loqman B Zainal Abidin, Ahmad Loqman (Universiti Teknologi Petronas, 2009)
The discovery in searching hydrocarbon has lately being changed from sonar technique to electromagnetic (EM) technique. The electromagnetic technique seems to be capable since the waves are carried by photons while the sonar is using sounds which need a medium since it is basically the vibration of particles. The Sea Bed Logging (SBL) is a method in searching hydrocarbon through electromagnetic theories and application. Throughout this report, the author will describe the approach by author in development of electromagnetic wave detection. There are 2 EM detectors that are going to be developed. The CNTs, well known for its excellent electrical and chemical properties is used for the EM detector development. The other EM detector is developed by synthesizing and fabrication process of zinc oxide with polymer based, ZnO-PVA. Both developed detectors are used to be analyzed and several experiments implemented to determine for better EM detector application. In short, this project including designing electromagnetic waves detectors and implementation of constructing the designs as well as the experimental parts. The success of this development could assist the continuous work and studies in searching for hydrocarbon.